Gibbs paradox and it’s solution - V. G. Kiselev (Известия высших учебных заведений: Проблемы энергетики, 2017)
The article deals with the classical solution of the Gibbs paradox, on the basis of which and experimentally verified the facts in the presence of the chemical energy of real gases and gases with properties approaching the ideal gases promoted the calculation of entropy of mixing in two ways ("physical" and "chemical"). As a result, found no discontinuity in the behavior of the value AS (entropy change) in the continuous convergence of parameters describing the mixed gases in the direction of the "ideal" in relation to a change in the entropy of mixing of ideal gases. Also identified as a lack of entropy change upon mixing of the same ideal gas and different ideal gases while maintaining their state of an ideal gas, and after mixing process.